Analisis Pengendalian Persediaan Obat Dengan Menggunakan Metode Analisis ABC, EOQ dan Reorder Point (Rop) (Studi Kasus: Rumah Sakit Umum Daerah (RSUD) Dr. Djasamen Saragih Pematangsiantar) - Bintang Sri M Siregar; Rektor Sianturi; Debora Exaudi Sirait (Jurnal Ilmu Pendidikan dan Sosial, 2024)
Inventory is one of the most important things in a company, especially in the hospital industry, in providing drug supplies in order to provide good services. So inventory contro is needed to avoid running out and excess stock of drugs. The aim of this research is to find out the grouping of drugs based on their investment value, find out the optimum order quantity for each drug and find out the time to order each drug. The research method used by researchers uses quantitative methods, ABC, EOQ and ROP analysis methods. This research was conducted at RSUD Dr. Djasamen Saragih Pematangsiantar. From the research resuts, the ABC analysis method shows that 14 types of group A drugs (23.3%) use a budget of 69% of the total drug budget usage, 13 types of group B drugs (21.7%) use a budget of 22%. Of the total use of the drug budget and types of group C drugs, 33 types (55%) use a budget of 9% of the total drug budget use. By analyzing the Economic Order Quantity (EOQ) method, the optimum number of drugs was obtained for group A from 31-2,651 items, group B starting from 6-2,438 items and group C starting from 8-5,527 items. Meanwhile, with ROP analysis, the drugs reordered for group A range from 16-851 items, group B starts from 1-398 items and group C starts from 1-819 items.